Tips for the science teacher : research-based strategies to help students learn - Hartman, Hope J.; Glasgow, Neal A. (Thousand Oaks, CA : Corwin Press, 2002)
Hartman and Glasgow decipher the latest educational research and translate it into practical and easy-to-use classroom applications that foster effective science learning and professional development. All facets of a scientific instructional program are explored, including emotional and social aspects of science learning, the use of technology and assessments in the classroom, the development of students' critical thinking and learning skills, and informal science learning. Other key highlights include: more than 90 practical tactics; user-friendly format in which each strategy is followed by a brief research recap, classroom applications, precautions, and references; and straightforward translation of educational research for easy integration into the classroom.
Instructional strategies -- Developing students' scientific thinking and learning skills -- Emotional aspects of science learning -- Social aspects of science classrooms -- Using technology in science teaching -- Informal science learning -- Assessment in the science classroom.
Includes bibliographical references and index.
Keywords: Science -- Study and teaching; Science teachers -- Training of